Blast resistance prediction of clay brick masonry wall strengthened with steel wire mesh, and C-FRP laminate under explosion loading: a finite element analysis. (27th January 2023) - Shariq, Mohd; Anas, S.M.; Alam, Mehtab
A detailed finite element micro-model of an Unreinforced Masonry (URM) wall of clay bricks, 1600 mm × 2100 mm × 240 mm, is made in ABAQUS/Explicit-v.6.15 code and analysed considering strain rate effects under the 5 kg-TNT explosion load at 0.58 m/kg 1/3 scaled distance in free air. Results are validated with the available blast test results. Strengthening of the wall is considered by providing (1) steel wire mesh of diameter 2.50, 3.50 and 4.50 mm on the (a) rear face only and (b) on both the faces; (2) C-FRP wrapping of a thickness (a) 0.50 mm (b) 0.60 mm on the rear face only and (c) 0.30 mm on both the faces of the wall. Response of wall with each strengthening technique applied in this study is discussed. Application of 4.50 mm wire mesh on both the faces and 0.50 mm C-FRP sheet on the rear face makes the wall respond with comparable performance under the considered blast loading.